2016
DOI: 10.1177/1756283x16663395
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and gastric acid: an intimate and reciprocal relationship

Abstract: Helicobacter pylori (Hp) is the main cause of gastritis, peptic ulcer disease and gastric cancer. There are still unanswered questions related to the interaction between Hp and man, like what determines the susceptibility for the initial infection and the mechanisms for the carcinogenic effect. The initial infection seems to require a temporal gastric hypoacidity. For Hp to survive in the gastric mucous layer, some acidity is necessary. Hp itself is probably not directly carcinogenic. Only when inducing oxynti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 68 publications
1
64
0
3
Order By: Relevance
“…The human intestine harbors nearly 100 trillion bacteria that are essential for health . Helicobacter pylori ( H pylori ) is a pathogen of GI diseases that can survive in the gastric juice . Previous reports found that H pylori infection causes changes in the normal physiological state of the GI flora, mental disorders via the vagus nerve, and alterations in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The human intestine harbors nearly 100 trillion bacteria that are essential for health . Helicobacter pylori ( H pylori ) is a pathogen of GI diseases that can survive in the gastric juice . Previous reports found that H pylori infection causes changes in the normal physiological state of the GI flora, mental disorders via the vagus nerve, and alterations in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, host interactions with H. pylori will improve allergic diseases and inflammatory bowel disease, especially in children [22]. Moreover, childhood H. pylori infection seems to be prevalent, which may be explained partly by reduced gastric acidity [23]. This phenomenon is significantly associated with abundant Treg cells compared to adults [24].…”
Section: The Different Characters Of Immune Cells In Inflammationmentioning
confidence: 99%
“…Due to the living environment and eating habits of the Chinese people, the Helicobacter pylori infection rate is higher in China than in developed countries, with an average H. pylori infection rate of 54.76% . Studies have found that H. pylori infection is closely related to functional dyspepsia, peptic ulcer, gastric cancer, gastric mucosa‐associated lymphoma and a variety of chronic gastritis and other gastrointestinal diseases . Studies thus far have mainly focused on the pathogenesis, prevention and treatment of the variety of gastrointestinal diseases caused by H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%